Internal Accounting Control Evaluation and Auditor Judgment (Book). - Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "Internal Accounting Control Evaluation and Auditor Judgment," by Theodore J. Mock and Jerry L. Turner.